2017
DOI: 10.1007/s12034-017-1438-5
|View full text |Cite
|
Sign up to set email alerts
|

Poly(acrylonitrile-co-itaconic acid)–poly(3,4-ethylenedioxythiophene) and poly(3-methoxythiophene) nanoparticles and nanofibres

Abstract: This work aimed to produce poly(acrylonitrile-co-itaconic acid) (P(AN-co-IA)) nanocomposites with poly(3,4ethylenedioxythiophene) (PEDOT) and poly(3-methoxythiophene) (PMOT). An anionic surfactant sodium dodecyl benzene sulphonate was used in emulsion polymerization for nanocomposite production. Incorporations of PEDOT and PMOT on the nanoparticles were characterized by scanning electron microscopy (SEM), atomic force microscopy, Fourier transform infrared-attenuated total reflectance spectroscopy and ultravio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…P (AN‐co‐IA) nanocomposite was synthesized by emulsion polymerization as described in our previous study as it was briefly shown as a scheme in Figure …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…P (AN‐co‐IA) nanocomposite was synthesized by emulsion polymerization as described in our previous study as it was briefly shown as a scheme in Figure …”
Section: Methodsmentioning
confidence: 99%
“…Characterization results revealed that changing amounts of NMPy has considerable effect on both dielectric properties and electromagnetic characteristics . Previously, morphological, spectroscopic, and electrochemical impedance studies were performed on P (AN‐co‐IA)/polythiophene nanocomposites and nanofibers obtained by electrospinning . Itaconic acid (IA) is among the comonomers preferred for generating nanocomposites with PAN since each monomer unit has two carboxylic groups leading to decrease of the melting and increase of the decomposition temperature of the copolymer .…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis of P(AN-co-IA) copolymer and PAN homopolymer P(AN-co-IA) copolymer was synthesized by emulsion polymerization utilizing water, SDBS and APS as dispersion medium, surfactant, and initiator, respectively. The polymerization was lasted for 3 h at 70 C and then stopped using ethanol and then cooled to room temperature as in previous studies [41][42][43]. The obtained emulsion latex was precipitated and washed with ethanol and water for five times.…”
Section: Experimental Materialsmentioning
confidence: 99%
“…Average diameter of the nanofibers was also determined using a special program, Image J. Figure 9 [43] shows SEM images of PAN and P(AN-co-IA) nanofibers along with their diameter distribution graphics. Figure 9 [43] shows that PAN and P(AN-co-IA) nanofibers are continuous, smooth, and fine with the average diameters of 120 and 132 nm, respectively.…”
Section: Sem and Edsmentioning
confidence: 99%
See 1 more Smart Citation